Energy consumption feedback devices' impact evaluation on domestic energy use (2013)
Household energy accounts for one of the major contributors to the countries energy balances. It has been shown, that an effective way to achieve energy saving in that sector, is by providing consumers with information and feedback. This measure increases home inhabitants' awareness that leads to behavioral changes, and could help reduce energy consumption between 15% and 25% in some cases. Inhabitants' energy use awareness is also crucial for the success of demand response programs; one of the most important features of smart-grid adoption for the current and upcoming smart cities.The effects of different feedback strategies and information devices in households located in different cities in Sweden have been evaluated in this paper, since the impact on users' behavior of this feedback information vary depending on the way it is provided.Mobile text messages (SMSs) and digital displays placed in the building's common areas did not cause any noticeable behavioral changes, while the use of a TV channel and personal in-home displays were the most popular devices amongst households with high incomes.This paper concluded that even though feedback helped reduce domestic energy consumption and induce behavioral changes, it only reaches the consumers interested in it. It is important therefore to provide customized information to the consumer and select precise feedback tools for specific household groups. Special attention should be paid to increasing the energy consumption awareness in households with low income levels. © 2013 Elsevier Ltd.